The Effect of Tool Rotation Speed Variation to Hardness and Microstructure in The Welding of Composite Alsitib-7,5%Sic by Friction Stir Welding Method - Farida, Ida; Sulardjaka, (International Journal of Psychosocial Rehabilitation, 2020)
Friction The stir welding method is a welding method which utilizes friction between rotating cutting tool that are pressed to material, so it will generate local heat and make material soften and will be integrated or merged. The aim of this study is to understand the effect of rotational speed (808 rpm, 1087 rpm, and 1570 rpm) on the hardness and microstructure of composite AlSiTiB-7.5%SiC welding by using a tool which has a conical pin shape and a welding speed of 0.02 mm/s. The results showed a significant increase in hardness value in the stir zone (nugget) region and TMAZ-HAZ interface region to hardness value of base metal. Rotational speed using 1087 rpm has the highest average value of hardness in the area of the stir zone (nugget) with a value of 126.4 HV, while at 808 rpm the hardness value is 118.1 HV and at 1570 rpm it is 74.6 HV. The microstructure result at 1087 rpm rotational speed showed no defects or wormhole occurred if compared with 808 rpm and 1570 rpm rotational speed, which have defects or wormholes.